Meningkatkan Kemampuan Menulis Puisi Menggunakan Metode Partisipatori melalui Media Gambar pada Siswa Kelas X IPA Semester II SMAN 9 Sarolangun Tahun Pelajaran 2020/2021 - Sumiharti Sumiharti; Sainil Amral; Ade Chudri Azuma (Universitas Batanghari Jambi, 2022)
This research is qualitative descriptive research with a type of class action research (PTK). Data collection is done with observation sheets and tests of student learning outcomes. The purpose of this study is to describe the ability to write poetry using participatory methods through image media in students of class X IPA Semester II SMAN 9 Sarolangun School Year 2020/2021 in an effort to improve poetry writing skills. The object of this study is writing poetry. The subjects in this study were students of class X IPA Semester II SMAN 9 Sarolangun School Year 2020/2021. The results of the study from data from 21 students, 18 students (85.7%) have met the completion of learning (school KKM) with an average score above 70 and 3 students (14.3%) who did not meet the completion of learning. If you look at it as a whole, with an average score of 82.14 obtained by students, it is clear that classically learning is complete. This percentage amount shows that the learning process in improving the ability to write poetry using participatory methods by using image media in cycle 2 is already underway to the maximum. Therefore, no further repair cycles are needed.